Catastrophe: Magic and History in Rural Madagascar - Graeber, David (Campos - Revista de Antropologia, 2004)
The essay recounts the beginning of my fieldwork in a Malagasy rural community an hours drive from the capital of Antananarivo in 1990. The community itself was, at the time I arrived, locked in a kind of intense symbolic warfare between andriana descended from what might be called a noble clan and mainty, the descendants of their former slaves. The struggle took on all the more significance when I came to understand that the Malagasy state had, for most intents and purposes, effectively withdrawn from such rural communities, but that members of those communities were engaged in a subtle game of appropriation of the representatives of what was seen as a predatory and coercive state power so as to fend it off, a habit that made the fact that rural communities were now effectively self-governing very difficult to perceive.